New contributions to the knowledge of the immatures of Stilobezzia punctulata Lane and Stilobezzia fiebrigi Kieffer (Diptera: Ceratopogonidae) - Cazorla, Carla Gisela (2013)
The fourth instar larva of Stilobezzia punctulata Lane is described for the first time and the one of Stilobezzia fiebrigi Kieffer is redescribed. They are illustrated and photomicrographed from material collected in different aquatic environments of the province of Corrientes, Argentina. Both species show features typical to carnivorous-predatory larva.